AN ANALYSIS OF POSSIBLE COMMON MENTAL DISORDERS AMONG HEALTHCARE PROFESSIONALS (CIPEEX, 2025)
Mental health among professionals working in the healthcare field is a growing concern, especially due to the demanding and stressful nature of their roles. These professionals, such as doctors, nurses, psychologists, and others, face a series of challenges in the workplace that can negatively impact their mental health. Among these challenges are the high workload, constant exposure to human suffering, the need to make critical decisions in a short amount of time, a lack of adequate resources, and insufficient support from healthcare institutions.The objective of this study was to analyze the mental health of healthcare professionals working in the cities of Ceres and Uruana, in the state of Goiás. To achieve this, the "Self Report Questionnaire (SRQ-20) - Test for assessing mental distress" was used as a research instrument, being applied in person at the workplaces of 20 healthcare professionals, aged between 29 and 45, residing in the mentioned cities.The analysis of the data obtained from the questionnaire revealed that 86% of the interviewed healthcare professionals showed signs of mental distress, which represents a significant proportion. These symptoms suggest that a large portion of healthcare professionals in these cities are facing working conditions that contribute to a high level of psychological distress. On the other hand, a small portion of the respondents, around 14%, did not present significant symptoms of psychological distress. Within this group, 10% of the participants did not check the "YES" option for any of the SRQ-20 questions, indicating an absence of mental distress symptoms.These results show that, although most professionals are vulnerable to mental health issues, some possess greater resilience or work in less stressful environments or perhaps have better support mechanisms and coping strategies. Strategies such as psychological support programs in the workplace, training for stress management, promoting a more welcoming work environment, and encouraging self-care practices are essential.The high prevalence of mental distress detected in this study highlights the need for public policies and institutional strategies that promote healthier and safer work environments. Investing in the mental health of these professionals is essential, not only for their well-being but also to ensure the quality of services provided to the population.
Keywords: mental health; healthcare professionals; srq-20